Listening to Clinical Teams: Developing Strategies to Support Sustained STAR-VA Implementation. (17th December 2021) - Page, Kyle; Benson, Karen; Wray, Laura; Karel, Michele; Curyto, Kim
Abstract: Feedback obtained from program evaluations and interviews with CLC team members who participated in STAR-VA helped to inform the development of sustained implementation strategies guided by the CFIR-ERIC Mapping Tool. A CLC readiness assessment was developed to guide selection of new champions and assess for local team readiness to implement STAR-VA. Virtual training materials were developed along with a champion training checklist to prepare additional champions and support team training. We identified key implementation steps and optional strategies to support sustained implementation, developed a sustained implementation guide, associated sustained implementation checklist, and sustainability toolkit. We are piloting a regional community of practice model, encouraging development of and building on relationship networks to promote use of program tools, collaborative problem-solving, feedback, and a shared vision for implementation. We will discuss the importance of tailored strategies for integrating new practices into usual care.